Gypenoside induces apoptosis by inhibiting the PI3K/AKT/mTOR pathway and enhances T-cell antitumor immunity by inhibiting PD-L1 in gastric cancer - Wu, Hongliang; Lai, Wenjing; Wang, Qiaoling; Zhou, Qiang; Zhang, Rong; Zhao, Yu (Frontiers in Pharmacology, 2024)
Introduction: Gypenoside is a natural extract of Gynostemma pentaphyllum (Thunb.) Makino, a plant in the Cucurbitaceae family. It has been reported to have antitumor effects on the proliferation, migration and apoptosis of various types of cancer cells. However, the use of gypenoside in the treatment of gastric cancer has not been studied. In the present study, we explored the therapeutic effect of gypenoside on gastric cancer and the potential molecular mechanism. Methods and Results: Our results showed that gypenoside induced apoptosis in HGC-27 and SGC-7901 cells in a time-dependent and dose-dependent manner. Network pharmacology analyses predicted that gypenoside exerts its therapeutic effects through the PI3K/AKT/mTOR signaling pathway. Furthermore, molecular docking and western blot experiments confirmed that gypenoside induced the apoptosis of gastric cancer cells through the PI3K/AKT/mTOR signaling pathway. In addition, network pharmacological analysis revealed that the common targets of gypenoside in gastric cancer were enriched in the immune effector process, PD-L1 expression, the PD-1 checkpoint pathway, and the Jak-STAT signaling pathway. Furthermore, molecular docking and western blot assays demonstrated that gypenoside could bind to STAT3 and reduce its phosphorylation. Thus, the transcription of PD-L1 was inhibited in gastric cancer cells. Moreover, coculture experiments of gastric cancer cells with gypenoside and primary mouse CD8+ T cells showed that gastric cancer cells treated with gypenoside could enhance the antitumor ability of T cells. Animal experiments confirmed the antitumor effect of gypenoside, and the expression of PD-L1 was significantly downregulated in the gypenoside-treated group. Conclusion: Gypenoside induced the apoptosis of gastric cancer cells by inhibiting the PI3K/AKT/mTOR pathway and simultaneously inhibited the expression of PD-L1 in gastric cancer cells, thus enhancing the antitumor immunity of T cells. This study provides a theoretical basis for applying gypenoside as a new therapeutic agent to enhance the efficacy of immunotherapy in gastric cancer.